Moderating Effect of Implementation Risk-Based Auditing on Audit Quality - Entar Sutisman, Yana Ermawati, Siti Mariani, Kartim, Aditya H. P. K. Putra (Jurnal Akuntansi, 2021)
This study aims to examine the effect of the ability and independence of auditors on audit quality by using risk-based auditing as a moderating variable at the Inspectorate of South Sulawesi Province. The population in this study were all auditors at the Inspectorate of South Sulawesi Province, using the purposive sampling method for sample selection so that 35 respondents were selected as samples. This research uses field research methods. This study used a survey method for field data collection, namely by distributing questionnaires to the research object. The statistical method used to test the hypothesis is to use multiple linear regression with the help of Smart PLS 3.0 software. The analysis results show that the ability and independence of the auditors have a positive and significant effect on audit quality. The application of risk-based auditing as a moderator of capability and freedom also positively impacts audit quality.